THE USE OF HUMAN RIGHTS INSTRUMENTS TO PROTECT THE VICTIMS OF LAND FIRE IN INDONESIA - Achmad Romsan; Akhmad Idris; Mada Apriandi Zuhir; Meria Utama (Faculty of Law, Universitas Sebelas Maret, 2018)
During the long and dry season, land fire which cause smog haze pollution, is a common phenomenon in Indonesia. Although the practice of slash and burn cultivation has no longer in existence after the promulgation of the 1974 Law No. 5 on the Village Government which abolished the Marga Government. Nevertheless, that tradition remained continued practiced by the workers hired by the big palm plantation companies and industries when they open the land to start their activities. it is very surprising that the above practice has resurfaced in the midst of a long dry season that is happening in Indonesia, especially in South Sumatra. Smog and haze resulting from land fire create health problems for the people in South Sumatra, especially in the area where smog and haze located. There are legal instruments as the foundation to claim the healthy environmental rights, the Indonesian Constitution of 1945, The 1999 Law No. 39 on Human Rights and the 2009 Law No. 32 on the Environmental Protection of and the Environmental Management. Herein, the smog and haze pollution are seen to violate the people’s human rights. Unfortunately, the use of human rights law instruments has never been done in Indonesia. Notwithstanding, many community environmental disputes are brought to the District Court rather than to the Indonesian Commission of Human Rights (KOMNAS HAM) for further study. As a result, the legal instruments above di not fully protect the victims of environmental pollution. This paper suggests the use of human rights provisions as the basis for prosecution for community environmental-human rights related disputes. For that, a comparative study to the practice of the European Human Rights Court will be of beneficial for Indonesia in protecting the people environmental human rights. In Indonesia the people’s right to a good and healthy environment is constitutional rights and legal rights for it is protected in the Human Rights Law of 1999 No. 39 and Environmental Law of 2009 No. 32. To that end, the human rights approach to the prosecution of environmental disputes are possible because of environmental pollution disturb the enjoyment of human rights.